Cabozantinib and IL-27 combinatorial therapy for bone-metastatic prostate cancer - Kumar, Shreya; Mulia, Grace E.; Figueiredo, Marxa L. (Frontiers in Molecular Biosciences, 2023)
Introduction: Prostate cancer is the second leading cause of cancer-related death among American men. Prostate tumor cells exhibit significant tropism for the bone and once metastasis occurs, survival rates fall significantly. Current treatment options are not curative and focus on symptom management. Immunotherapies are rapidly emerging as a possible therapeutic option for a variety of cancers including prostate cancer, however, variable patient response remains a concern. Chemotherapies, like cabozantinib, can have immune-priming effects which sensitize tumors to immunotherapies. Additionally, lower doses of chemotherapy can be used in this context which can reduce patient side effects. We hypothesized that a combination of chemotherapy (cabozantinib) and immunotherapy [Interleukin-27 (IL-27)] could be used to treat bone-metastatic prostate cancer and exert pro-osteogenic effects. IL-27 is a multi-functional cytokine, which promotes immune cell recruitment to tumors, while also promoting bone repair. Methods: To test this hypothesis, in vivo experiments were performed where syngeneic C57BL/6J mice were implanted intratibially with TRAMP-C2ras-Luc cells that are able to form tumors in bone. Immunotherapy was administered in the form of intramuscular gene therapy, delivering plasmid DNA encoding a reporter gene (Lucia), and/or a therapeutic gene (IL-27). Sonoporation was used to aid gene delivery. Following immunotherapy, the animals received either cabozantinib or a vehicle control by oral gavage. Bioluminescence imaging was used to monitor tumor size over time. Results: Combinatorial therapy inhibited tumor growth and improved survival. Further, RNA sequencing was used to investigate the mechanisms involved. Microcomputed tomography and differentiation assays indicated that the combination therapy improved bone quality by enhancing osteoblast differentiation and inhibiting osteoclast differentiation. Discussion: Our conclusion is that a chemo-immunotherapy approach such as the one examined in this work has potential to emerge as a novel therapeutic strategy for treating bone-metastatic prostate cancer. This approach will enable a significant reduction in chemotherapy-associated toxicity, enhance sensitivity to immunotherapy, and improve bone quality.